Year 2 Bilingual Terminology Mathematics - Tay, Choo Chuan (Penerbitan Daya Sdn. Bhd.(188832-X), 2013)
Year 2 Bilingual Terminology Mathematics based on the latest KBSR Mathematics Syllabus. All the terms are selected from the textbook and sentences related to the terms are bilingual